Pengaruh Current Ratio (CR) dan Total Asset Turnover terhadap Return On Asset (ROA) pada Perusahaan Sub Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia ( 2020-2024) - Putri Ayu Diah Astuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
ROA in the company's financial performance generates profit from total assets owned can be seen from the current ratio and total asset turnover. This study aims to analyze the effect of Current Ratio and Total Asset Turnover on Return On Asset in Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2020- 2024. This research method is a quantitative statistical research of data types, secondary data. Purposive Sampling sampling technique. The results of this study indicate that Current Ratio (XI) has a significant effect on Return On Asset (Y) with a t-count value > 1-table, namely 4. 416-1.760, and a probability value of t-statistics of 0.000 < 0.05, Total Asset Turnover (X2) does not have a significant effect on Return on Assets (Y) with a t-table value of (0.892 < 1.760) and a probability value of 0.374 > 0.05., The results of the simultaneous Current Ratio and Total Asset Flow on Return On Assets have an effect on Return On Assets. This is indicated by the F-statistic F- table of (10.093 > 3.37) and the probability value of F-statistics of 0.000 < 0.05. The coefficient of determination (R²) is 63.3%